Factors influencing sustainability of online platforms for professionals: a mixed-method study in OECD countries. (3rd May 2021) - Hubertus Bessems, Kathelijne Maria Hubertus; Simovska, Venka; Driessen Willems, Marion Daniëlle; Carlsson, Monica; de Vries, and Nanne K
Summary: Online platforms can support health and educational professionals in their daily work; however, it is challenging to keep online platforms sustainable. This paper aims to indicate the most important factors of platform sustainability from the perspective of professionals involved in online platforms. Further, it aims to understand how these factors operate. A mixed methods study was carried out among professionals from Europe, Australia, the USA and Canada. In the first phase, the importance of 54 factors from the literature was assessed with a questionnaire among 17 professionals. The relative importance of the factors and the consensus regarding this importance were calculated using median scores and interquartile deviations. In total, 19 factors were selected representing general characteristics, characteristics related to the platform, communication, visitor and context. In the second phase, insight was gained regarding the experiences with those factors through 12 individual Skype interviews. The most frequently mentioned important factors of platform sustainability were (i) having sufficient time, resources and expertise, (ii) user friendliness and (iii) creating a sense of belonging. Platforms should use a planned approach to address a combination of factors directly from platform development. Gaining long-term resources is challenging and should be considered from the start of a project by building partnerships. To promote user friendliness, platforms should be simple, have a clear set-up and provide high-quality tools. Finally, establishing a sense of belonging could be supported by branding and face-to-face networking activities. For all aspects, involving visitors and stakeholders is essential.